Comparing forward and reverse transfer from Dutch to German. (August 2022) - Barking, Marie; Mos, Maria; Backus, Ad
Aims and objectives/purpose/research questions: This study compares transfer from Dutch to German by native Dutch speakers who learned German as a second language (forward transfer: L1 to L2) and by native German speakers who are living in the Netherlands (reverse transfer: L2 to L1). The aim of this comparison is to see whether both groups experience the same kind of transfer (i.e., transferring the Dutch preference for prepositional phrases in the postfield position to German) and whether the extent of transfer depends on their language use. Design/methodology/approach: We compiled a corpus (2, 908, 154 words) consisting of German e-mails written by native Dutch speakers ( n = 21) and native German speakers living in the Netherlands ( n = 9). In addition, speakers filled in the BLP (bilingual language profile) test. Data and analysis: The corpus was analyzed for the speakers' placement of prepositional phrases, and we linked their answers on the BLP test to their language use in the corpus data. Findings/conclusions: Our data show that the native Dutch speakers use the postfield position more frequently in their German than the native German speakers do. Besides, for both groups, the postfield use was related to the speakers' use of Dutch as well as German varieties that are influenced by Dutch. Originality: This study directly compares forward and reverse transfer using a large corpus of written German texts, and it links both types of transfer to the speakers' language use. In doing so, the study shows that the mechanism of entrenchment is likely to underlie transfer in both cases. Significance/implications: The results of this study are in line with a usage-based approach: there is extensive individual variation between speakers regarding their extent of transfer, which partly can be attributed to the speakers' language use, both in the case of forward and reverse transfer.